Answer:
1 and 4 has same pairs of solution.
Step-by-step explanation:
Solutions for the given equations are:
\begin{gathered}1. (x+6)(x - 6) = 0\\(x+6) = 0, (x-6) = 0\\x = -6, x = 6\\\\2. (x + 6)(x + 6) = 0\\(x+6) = 0, (x+6) = 0\\x = -6, x = -6\\\\3. (x - 6)(x - 6) = 0\\(x-6) = 0, (x-6) = 0\\x = 6, x = 6\\\\4. (2x + 12)(2x - 12) = 0\\(2x+12) = 0, (2x-12) = 0\\x = -6, x = 6\\\\5. (2x - 12)(x - 12) = 0\\(2x-12) = 0, (x-12) = 0\\x = 6, x = 12\\\\6. (x+12)(x - 12) = 0\\(x+12) = 0, (x-12) = 0\\x = -12, x = 12\\\\7. (x +12)(x-6) = 0\\(x+12) = 0, (x-6) = 0\\x = -12, x = 6\end{gathered}
1.(x+6)(x−6)=0
(x+6)=0,(x−6)=0
x=−6,x=6
2.(x+6)(x+6)=0
(x+6)=0,(x+6)=0
x=−6,x=−6
3.(x−6)(x−6)=0
(x−6)=0,(x−6)=0
x=6,x=6
4.(2x+12)(2x−12)=0
(2x+12)=0,(2x−12)=0
x=−6,x=6
5.(2x−12)(x−12)=0
(2x−12)=0,(x−12)=0
x=6,x=12
6.(x+12)(x−12)=0
(x+12)=0,(x−12)=0
x=−12,x=12
7.(x+12)(x−6)=0
(x+12)=0,(x−6)=0
x=−12,x=6
(x+6)(x - 6) = 0 and (2x + 12)(2x - 12) = 0 have same pair of solutions.
Step-by-step explanation:
there you go :)
Let’s take a random number such as 10, for example as the divisor of the equation.
Let’s take the dividend, or numerator of the fraction be x.
The solution of the fraction would be -2.
x/10 = -2
Or, x= -2 x 10
Or, x= -20
Therefore, -20/10 = -2
Ans: The division equation would be -20/10 = -2.
Answer:
-13
Step-by-step explanation:
Subsitude -2 to where x is and you get -1o then subtract by -3 and the total is -13
Answer:
X+Y=26
X-Y=12
Step-by-step explanation:
fiction books= X
non fiction books= Y
then,
fiction books= X
non fiction books = X-12
but Y= X - 12
from. the statement,
X+Y = 26
X-Y=12
Answer: c
Step-by-step explanation:
Yea